2022
DOI: 10.1002/nop2.1270
|View full text |Cite
|
Sign up to set email alerts
|

Patients' expectations and experiences of provided surgery‐related patient education: A descriptive longitudinal study

Abstract: Aims The aim of this study was to explore the educational expectations and experiences of surgical patients. Design Prospective, longitudinal, descriptive and two‐centre study. Data were collected with questionnaires at the hospital and 6 weeks and 6 months postsurgery. Methods Patients undergoing elective surgery and hospitalized overnight from January to July 2016 answered questions about the content of received pre‐operative and pre‐discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
2
5
0
3
Order By: Relevance
“…Improved 30-day readmission rates post–cardiac arrhythmia ablation procedure were observed on the basis of the significantly lower 30-day readmission rate in the intervention group than in the control group that did not receive the educational intervention. This pilot study supports findings in the literature that had shown a reduction in 30-day postsurgical readmission rates with implementation of increased patient education 25. Support for use of the phone call as a method for delivering the enhanced education intervention evolved from studies showing that the most vulnerable period postoperatively for readmission is 24 to 72 hours after discharge27 and that implementation of a phone call during this time period to assess patients' knowledge and needs during this acute discharge period can prevent unnecessary readmissions 28…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Improved 30-day readmission rates post–cardiac arrhythmia ablation procedure were observed on the basis of the significantly lower 30-day readmission rate in the intervention group than in the control group that did not receive the educational intervention. This pilot study supports findings in the literature that had shown a reduction in 30-day postsurgical readmission rates with implementation of increased patient education 25. Support for use of the phone call as a method for delivering the enhanced education intervention evolved from studies showing that the most vulnerable period postoperatively for readmission is 24 to 72 hours after discharge27 and that implementation of a phone call during this time period to assess patients' knowledge and needs during this acute discharge period can prevent unnecessary readmissions 28…”
Section: Discussionsupporting
confidence: 89%
“…This study shows that diagnosis-specific discharge instruction positively impacts patient satisfaction, which is a measure of quality of care. These findings support knowledge described in the literature that successful patient education interventions such as this are linked to higher rates of patient satisfaction 24,25. It is also important to note that calls in this study were made by the NP and literature has shown that compared with physicians, NPs place greater emphasis on symptom identification and are more likely to advise and schedule follow-up appointments 26…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Due to the relative novelty of these techniques, there exists a plethora of validated literature for surgeons to review, but not for patients about to undergo BPI surgery. Patient education plays a significant role in this context, as patients need knowledge to make health-related decisions and manage their health, before and after the surgery, for optimal recovery (Blondal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%